A case study for the formation of stanene on a metal surface - Maniraj, Mahalingam; Stadtmüller, Benjamin; Jungkenn, Dominik; Düvel, Marten; Emmerich, Sebastian; Shi, Wujun; Stökl, Johannes; Lyu, L.; Kollamana, J.; Wei, Z.; Jurenkow, A.; Jakobs, S.; et al. (Technische Universität Dortmund, 2019)
The discovery and realization of graphene as an ideal two-dimensional (2D) material has triggered extensive efforts to create similar 2D materials with exciting spin-dependent properties. Here, we report on a novel Sn 2D superstructure on Au(111) that shows similarities and differences to the expected electronic features of ideal stanene. Using spin- and angle-resolved photoemission spectroscopy, we ﬁnd that a particular Sn/Au superstructure reveals a linearly dispersing band centered at the Γ-point and below the Fermi level with antiparallel spin polarization and a Fermi velocity of vF ≈ 1×106 m/s, the same value as for graphene. We attribute the origin of the band structure to the hybridization between the Sn and the Au orbitals at the 2D Sn-Au interface. Considering that free-standing stanene simply cannot exist, our investigated structure is an important step towards the search of useful stanene-like overstructures for future technological applications.
Communications physics;Vol. 2. 2019, 12:1-9
Keywords: Electronic devices; Electronic properties and materials; Surfaces, interfaces and thin films; Topological insulators; Two-dimensional materials; 530